STYLISTIC FEATURES AND THEIR TRANSLATION IN “STARRY NIGHTS” BY PRIMQUL QODIROV (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This paper analyzes the stylistic features of the Uzbek novel “Yulduzli tunlar” by Primqul Qodirov and its English translation (Starry Nights). The study focuses on metaphor, tone, sentence structure, and imagery. It examines how these elements are preserved or altered in translation. The findings show that while the semantic meaning is largely maintained, the poetic richness and emotional nuance of the original text are partially reduced in translation.
Keywords: Translation, metaphor, stylistics, Uzbek literature, equivalence, imagery, tone